Optimization of Welding Parameters for Small-Scale Resistance Spot Welding of Zirconium Alloys; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Slobodyan M. S. Mikhail Stepanovich (2019, 2019)
Title screen